Contributions of intense physical activity and sport to successful aging in a sample of spanish old people - Alberola, Salvador (2025)
High-intensity physical activity and sports properly performed can be sources of health benefits for older people. However, the socioemotional aspects of training needs to be investigated because it may be overly focused on improving execution and performance, especially in older people who compete. In the present investigation, we intend to observe the possible contributions of the practice of high-intensity physical activity and sports to successful aging. For this purpose, a cross-sectional observational study with incidental sampling of N=120 Spanish elderly (aged 60 years or older) was carried out. The level of intensity of physical activity was measured and scores on the different dimensions of successful aging and related variables were observed, there was the fact that people who practiced high intensity physical activity had a higher level of physical self-care. Thus, new evidence was provided that the performance of intense physical activity and sports during aging may contribute to the self-care of the older people, and this may help to have a more successful aging. Finally, it was suggested that training older people with intense physical activity and sports should focus on promoting aspects such as self-care and socialization.